The Role of Communities of Practice in Increasing Organizational Maturity Levels towards Digital Transformation: Case Study of Employee Cooperative - Marcel Marcel; Meyliana Meyliana; Spits Warnas Harco Leslie Hendric; Tirta Nugraha Mursitama (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
Organizations looking to improve operational efficiency, customer service and innovation begin by embarking on digital transformation journey. Such transformation necessitates a radical shift in the way organizations execute and behave. Communities of Practice (CoPs) are central to this wavy journey towards agility. This paper presents the role of CoP to assist in advancing organizational maturity quality for successful digital transformation, focusing from a social learning perspective. This paper conducted a case study with an employee cooperative of one state-owned enterprise based in Jakarta, Indonesia using literature reviews and semi-structured interviews involving the perspective from managers, IT staffs as well general staff. This paper utilized the Deloitte Digital Maturity Model (DMM) to evaluate digital maturity levels in five areas: Strategy, Culture, Organization, Technology and Customer. Results suggest that CoPs encourage a learning, innovative culture supported by management strong support and flexible structures with digital collaboration tools embedded in this comprehensive structure as well purposeful continuous training. The cooperative's digital maturity is in the initial stages, with five areas identified for improvement in strategy integration, cultural openness, organizational structure, technological adoption, and customer engagement. This research underlines that CoPs play an important role in enabling collaborative learning as well as digital maturity. Future research could elaborate on the long-term consequences of CoP and extend comparisons across various industries as well as consider how emerging technology influences a variety of factors related to effectiveness of CoPs.